2008
DOI: 10.1097/jom.0b013e318188b8eb
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Metabolic Syndrome in an Employed Population and the Impact on Health and Productivity

Abstract: Metabolic syndrome was associated with poor perceived health, increased illness days, and an increased trend of STD incidence. Worksite health promotion programs could be useful in helping employees and employers to identify metabolic syndrome risks and take steps to reduce risk and potential productivity losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
2
34
1
1
Order By: Relevance
“…There were no studies that reported workers in mining or agricultural. Three studies reported findings from single employers [28,29,31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no studies that reported workers in mining or agricultural. Three studies reported findings from single employers [28,29,31].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of the above psychometrically sound instruments [33] and even a cardiac specific tool-the Angina-Related Limitations at Work Questionnaire [34]; none used disease-specific instruments and several studies described measuring presenteeism using study-specific measures. [25,26,28,35] Only Munir [35,36] and Lerner [37] reported study specific instrument psychometrics. This is a notable limitation in this area of research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses from the general population have revealed excessive weight gain (WG) as an important risk factor for developing metabolic syndrome (MetS) [2,3] . MetS is also becoming an important concern in workplaces [4][5][6] for its impacts on both the health condition [7] and productivity [8] of employees. Excessive WG is common in the early-middle-aged population [9,10] who account for the majority of the workforce.…”
Section: Introductionmentioning
confidence: 99%